Additive manufacturing of fine-grained high-strength titanium alloy via multi-eutectoid elements alloying. (15th January 2023) - Su, Jinlong; Jiang, Fulin; Tan, Chaolin; Weng, Fei; Ng, Fern Lan; Goh, Min Hao; Xie, Haiming; Liu, Jin; Chew, Youxiang; Teng, Jie
Abstract: Developing fine-grained high-strength titanium (Ti) alloys by additive manufacturing has boomed interest for both research and application. The eutectoid element addition has been demonstrated as a feasible approach; however, solid solubility of the eutectoid elements in Ti alloys is limited, and the excessive eutectoid element addition could form brittle intermetallics and thereby deteriorating the ductility. To address this challenge, here we demonstrate a novel multi-eutectoid elements alloying approach based on thermodynamic prediction to achieve refined microstructure and high strength in Ti alloys. The trace eutectoid alloy elements Co, Cr, and Ni were in-situ alloyed with the Ti–6Al–4V alloy synergistically through laser-directed energy deposition. Moreover, a heterostructured titanium alloy was also fabricated by manipulating the spatial distribution of the eutectoid elements. Interestingly, the multiple eutectoid elements contribute to the in-situ decomposition of α ′, thereby bringing a favourable ultrafine α/β microstructure. Tensile strength of ∼1.34 GPa and ductility of ∼5.1% are attained with eutectoid elements addition, suggesting a superior combination of strength and ductility. The mechanisms regarding grain refinement, variant selection, strengthening, and toughening were investigated intensively. This work could provide significant guidance for microstructure engineering and performance enhancement in additively manufactured Ti alloys. Graphical abstract: Image 1 Highlights: Multi-eutectoid elements alloying strategy guided by thermodynamic prediction. Multiple eutectoid elements accelerate decomposition of α ′ during additive manufacturing. Superior strength and ductility synergy in Ti alloy by multi-eutectoid elements alloying. Mechanistic studies on grain refinement, variant selection, strengthening and toughening.